Effortless inhibition: habit mediates the relation between self-control and unhealthy snack consumption - Adriaanse, Marieke A.; Kroese, Floor M.; Gillebaart, Marleen; De Ridder, Denise T. D. (Frontiers in Psychology, 2014)
In contrast to prevailing beliefs, recent research suggests that trait self-control promotes health behavior not because those high in self-control are more successful at resisting single temptations, but rather because they develop adaptive habits. The present paper presents a first empirical test of this novel suggestion by investigating the mediating role of habit in explaining the relation between self-control and unhealthy snacking behavior. Results showed that self-control was negatively associated with unhealthy snack consumption and unhealthy snacking habits. As hypothesized, the relation between self-control and unhealthy snack intake was mediated by habit strength. Self-control was not associated with fruit consumption or fruit consumption habits. These results provide the first evidence for the notion that high self-control may influence the formation of habits and in turn affect behavior. Moreover, results imply that self-control may be particularly influential in case of inhibiting unhealthy food intake rather than promoting healthy food intake.